Femme-Castratrice in Si Manis Jembatan Ancol (2019) - Natashi Gracia Ireneke (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This thesis aims to know how the lead female character in Si Manis Jembatan Ancol (2019) fulfills the characteristics of a femme-castratrice and also to see the result that the lead character gets after she transforms into a female monster. To address the questions, I will use the monstrous-feminine theory as the main theory to be applied to Maryam as a victim of gender-based violence. From this theory, I want to show that the transformation of a femme-castratrice may occur by symbolic and literal castration. The symbolic castration means that the victim is castrated emotionally, whereas the literal castration means that the victim is physically abused. I connected the analysis with the abjection theory to show the result and resolution once the main female character is fully transformed into a femme-castratrice, which is a total banishment from the disturbed society, in a form of annihilation. In the end, it can be concluded that a femme-castratrice in Si Manis Jembatan Ancol (2019) is considered an ambiguous character.